Climate‐influenced migration in Bangladesh: The need for a policy realignment. (26th September 2017) - Martin, Maxmillan; Kang, Yi hyun; Billah, Motasim; Siddiqui, Tasneem; Black, Richard; Kniveton, Dominic
Abstract: Recent research into migration in Bangladesh has highlighted that people migrate for better livelihoods, not necessarily in response to climatic stresses and shocks. If facilitated appropriately, internal and international migration can help build adaptive capacity to future environmental and climatic hazards. In this framing, migration happens in the context of a growing city‐centred economy that promotes remittances to villages. However, a textual analysis of current and recent policies concerning climate change, development and poverty alleviation, and disaster management shows that the economic and adaptive roles of internal migration are often not included in policy framing. We argue that if migration works as a positive step towards adaptation, then the key challenge is to align the policies with this new understanding.